2016
DOI: 10.1007/s12022-016-9437-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Clinicopathologic and Radiographic Findings Between TT-UMP, Classical, and Non-Encapsulated Follicular Variants of Papillary Thyroid Carcinomas

Abstract: Thyroid tumors of uncertain malignant potential (TT-UMP) comprise an accepted subgroup of follicular-patterned thyroid tumors for which benignancy or malignancy cannot be precisely assessed. We aimed to evaluate the demographic characteristics, ultrasound (US) findings, and cytological results of patients with TT-UMP and compare these findings to a classical variant of papillary thyroid carcinoma (CV-PTC) and non-encapsulated follicular variant of PTC (NEFV-PTC) patients; we also evaluated the immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…We also compared the previous matched FNAC diagnosis for the histopathology diagnosis of NIFTP, both in our current study and in previously published reports (Table ) . For the benign category, NIFTP correlations with prior FNA diagnosis varied widely (benign, 0%‐30.4%; AUS/FLUS, 5.2%‐61%; FN/SFN, 3.9%‐40.6%; SM, 0%‐41.5%; and M, 0%‐12.7%).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…We also compared the previous matched FNAC diagnosis for the histopathology diagnosis of NIFTP, both in our current study and in previously published reports (Table ) . For the benign category, NIFTP correlations with prior FNA diagnosis varied widely (benign, 0%‐30.4%; AUS/FLUS, 5.2%‐61%; FN/SFN, 3.9%‐40.6%; SM, 0%‐41.5%; and M, 0%‐12.7%).…”
Section: Resultsmentioning
confidence: 83%
“…The reporting rate of NIFTP on histopathology is quite variable in the published data, 17,18,23,[25][26][27][28] which may be caused by multiple factors, including patient demographics, referral patterns, and the diagnostic threshold of individual cytopathologists and surgical pathologists. Currently, FVPTC represents a significant proportion (approximately 15%-20%) of PTC diagnoses with increasing incidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the microfollicular architecture of NIFTP, cPTC cells are distributed chiefly in sheets and papillae, and show prominent nuclear features including grooves and more frequent and easily identifiable INI, and psammomatous calcification . cPTC is more likely to be categorised into the highest TBSRTC categories (SFM and malignant) as compared to NIFTP, which usually falls into one of the intermediate categories (AUS/FLUS, FN/SFN, SFM; Table ) . We compared NIFTP cytology with that of cPTC showing a predominant follicular pattern (PTC‐FP).…”
Section: Discussionmentioning
confidence: 99%
“…Studies to date have shown that cytomorphologically, NIFTPs tend to show a predominant microfollicular architecture composed of cells with irregular nuclear borders and chromatin clearing and an absence of papillae and pseudoinclusions . Since NIFTPs or their former equivalent (NEFVPTCs) typically do not show the full range of nuclear features seen in classic type PTCs, particularly when the atypia is subtle or focal, they are frequently assigned an indeterminate cytological diagnosis within the TBSRTC classification system (Table ). In our study, of the 72 cases of NIFTP with a prior cytological diagnosis, 40.3% were classified as AUS/FLUS and 37.5% as FN/SFN/FNOF.…”
Section: Discussionmentioning
confidence: 99%